2017
DOI: 10.1021/acs.jpclett.7b03048
|View full text |Cite
|
Sign up to set email alerts
|

From Solvent-Free to Dilute Electrolytes: Essential Components for a Continuum Theory

Abstract: The increasing number of experimental observations on highly concentrated electrolytes and ionic liquids show qualitative features that are distinct from dilute or moderately concentrated electrolytes, such as self-assembly, multiple-time relaxation, and under-screening, which all impact the emergence of fluid/solid interfaces, and transport in these systems. Since these phenomena are not captured by existing mean field models of electrolytes, there is a paramount need for a continuum framework for highly conc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 68 publications
(254 reference statements)
1
110
0
Order By: Relevance
“…Such oscillations were predicted much earlier by Kirkwood [12], and the crossover at the onset of oscillations is known as the Kirkwood line. We note that charge oscillations emerge also from several Ginzburg-Landau-type theories that are used, for example, to describe the charge density of ionic liquids in the proximity of charged surfaces [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 94%
“…Such oscillations were predicted much earlier by Kirkwood [12], and the crossover at the onset of oscillations is known as the Kirkwood line. We note that charge oscillations emerge also from several Ginzburg-Landau-type theories that are used, for example, to describe the charge density of ionic liquids in the proximity of charged surfaces [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Gavish et al [42] and Rotenberg et al [43] suggested alternative theoretical explanations of the underscreening effect. Their arguments were based, respectively, on the phenomenological density-functional approach and the mean-spherical approximation.…”
Section: Nature Of Compacity and Overscreening Vs Underscreeningmentioning
confidence: 99%
“…The monotonic decay is captured with mean-field theories [12,67]. While the oscillating component could be interpreted as ion pair orientation [87]. Hence, from introducing spectating ions, which represent ion pairs and neutral aggregates, we can include some effects of strongly correlated systems [13][14][15][16]87].…”
Section: Basic Equations and Conceptsmentioning
confidence: 99%